In vitro and in vivo experimental trials to assess the modulatory influence of β-caryophyllene on NDV replication and immunopathogenesis. (December 2020) - Hassanin, Ola; Abdallah, Fatma; A.A.Galal, Azza
Highlights: In an ovo model β-Caryophyllene possesses antiviral efficacy when treated before or during NDV infection. Oral supplementation of chickens with β-Caryophyllene resulted in a significant increase in NDV HI-Ab responses 3–4 weeks post vaccination. β-Caryophyllene supplementation led to a significant increase in interferon-α transcription and its signaling cytokines elicited post NDV vaccination. β-Caryophyllene minimized NDV replication and reduced shedding titer from the oropharyngeal route. Abstract: A trial was conducted to evaluate the antiviral activity and immunomodulatory effect of B-Caryophyllene (BCP) using NDV as a viral model. First, an in ovo experiment was conducted to estimate the antiviral mechanism of BCP. Next, an in vivo experiment was designed to confirm its antiviral efficacy as well as its immunomodulatory and growth promoting ability. According to the in ovo experiment, BCP possesses antiviral influence up to 61.7% when treated before or during NDV infection. Oral supplementation of chickens with two doses of BCP (200 and 400 μg/bird) resulted in a significant increase in the NDV HI-Ab responses and a significant increase in interferon-α signaling cytokines. These obvious immunomodulatory effects improved the bird clinical protection against virulent NDV challenge. To conclude, we introduced a new compound for the poultry industry sector that has antiviral and immunostimulant properties when supplemented orally before or during NDV infection.